Climate change and perishable food hoards of an avian predator: Is the freezer still working?. (1st August 2020) - Masoero, Giulia; Laaksonen, Toni; Morosinotto, Chiara; Korpimäki, Erkki
Abstract: Changing climate can modify predator–prey interactions and induce declines or local extinctions of species due to reductions in food availability. Species hoarding perishable food for overwinter survival, like predators, are predicted to be particularly susceptible to increasing temperatures. We analysed the influence of autumn and winter weather, and abundance of main prey (voles), on the food‐hoarding behaviour of a generalist predator, the Eurasian pygmy owl ( Glaucidium passerinum ), across 16 years in Finland. Fewer freeze–thaw events in early autumn delayed the initiation of food hoarding. Pygmy owls consumed more hoarded food with more frequent freeze–thaw events and deeper snow cover in autumn and in winter, and lower precipitation in winter. In autumn, the rotting of food hoards increased with precipitation. Hoards already present in early autumn were much more likely to rot than the ones initiated in late autumn. Rotten food hoards were used more in years of low food abundance than in years of high food abundance. Having rotten food hoards in autumn resulted in a lower future recapture probability of female owls. These results indicate that pygmy owls might be partly able to adapt to climate change by delaying food hoarding, but changes in the snow cover, precipitation and frequency of freeze–thaw events might impair their foraging and ultimately decrease local overwinter survival. Long‐term trends and future predictions, therefore, suggest that impacts of climate change on wintering food‐hoarding species could be substantial, because their 'freezers' may no longer work properly. Altered usability and poorer quality of hoarded food may further modify the foraging needs of food‐hoarding predators and thus their overall predation pressure on prey species. This raises concerns about the impacts of climate change on boreal food webs, in which ecological interactions have evolved under cold winter conditions. Abstract : In autumn, pygmy owls delayed their food hoarding with few freeze–thaw events, the rotting of food hoards increased with precipitation and rotten hoards were used more in years of food scarcity than in years of high food abundance. Having rotten food hoards in autumn resulted in a lower future recapture probability of females. Pygmy owls might be partly able to adapt to climate change by delaying the initiation of food hoarding, but changes in snow cover, precipitation and frequency of freeze–thaw events might impair their hoarding behaviour and the perishability of hoarded food and ultimately decrease local overwinter survival.